2010
DOI: 10.1371/journal.pone.0008925
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction of Saccharomyces boulardii with Salmonella enterica Serovar Typhimurium Protects Mice and Modifies T84 Cell Response to the Infection

Abstract: Background Salmonella pathogenesis engages host cells in two-way biochemical interactions: phagocytosis of bacteria by recruitment of cellular small GTP-binding proteins induced by the bacteria, and by triggering a pro-inflammatory response through activation of MAPKs and nuclear translocation of NF-κB. Worldwide interest in the use of functional foods containing probiotic bacteria for health promotion and disease prevention has increased significantly. Saccharomyces boulardii is a non-pathogenic yeast used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 30 publications
10
79
0
Order By: Relevance
“…Although the adhesion phenomenon has been clearly demonstrated and visualized in vitro in the present study as well as in previous preliminary reports (Gedek, 1999;Pérez-Sotelo et al, 2005;Martins et al, 2010Martins et al, , 2011, it is not known whether it occurs in vivo. For this purpose, an animal model using germ-free mice was used to confirm and visualize the interaction between the yeast and the pathogenic bacterium on the intestinal epithelium.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although the adhesion phenomenon has been clearly demonstrated and visualized in vitro in the present study as well as in previous preliminary reports (Gedek, 1999;Pérez-Sotelo et al, 2005;Martins et al, 2010Martins et al, , 2011, it is not known whether it occurs in vivo. For this purpose, an animal model using germ-free mice was used to confirm and visualize the interaction between the yeast and the pathogenic bacterium on the intestinal epithelium.…”
Section: Discussionsupporting
confidence: 57%
“…Many mechanisms of action have been proposed to explain yeast probiotic protection against bacterial infection, such as modulating the immune system (Buts et al, 1990;Rodrigues et al, 2000), degrading Clostridium difficile toxins A and B and their respective receptors on colonic mucosa (Castagliuolo et al, 1999;Qamar et al, 2001), inhibiting cholera toxin action (Czerucka et al, 1994;Brandão et al, 1998) and modulating the transduction pathway when activated by enteropathogenic bacteria (Czerucka et al, 2000;Dahan et al, 2003;Martins et al, 2010Martins et al, , 2011. Another frequently cited mechanism for probiotic action is the production of diffusible antagonistic compounds inhibiting pathogenic bacterial growth.…”
Section: Introductionmentioning
confidence: 99%
“…onstrated that in addition to PagN, Rck, and T3SS-1, other invasion factors are capable of promoting Salmonella zipper or trigger entry, perhaps involving distinct active Rho GTPases that Y. enterocolitica effectors are incapable of inactivating (17,59). The ability of Y. enterocolitica to inhibit S. Typhimurium uptake is in agreement with a recent study conducted by Martins et al that shows that incubation of HeLa cells overnight with the yeast Saccharomyces boulardii reduced S. Typhimurium uptake (69). In this study, Rac1 and Cdc42 were found to be downregulated by S. boulardii.…”
Section: Discussionsupporting
confidence: 89%
“…The potential mechanisms by which probiotic agents might exert their protective effect include: antagonism by the production of substances that inhibit or kill the pathogen, competition with the pathogen for adhesion sites or nutritional sources; immunemodulation of the host; and inactivation of microbial toxin (Other mechanisms by which probiotics may exert protection is through a recuperation of mucosal barrier function when disturbed, trapping pathogens on their surface and stimulating mucus production, specific probiotic bacteria have been reported to modulate local and systemic immune responses [20][21][22][23][24]. Although the mechanisms of immune modulation are not fully understood it is known that bacterial components are recognized by the immune system through their interaction with specific Toll-like receptors resulting in the modulation of immune responses [25].…”
Section: Bacterial Probioticsmentioning
confidence: 99%